Erratum: The article „Morphometric analysis of collagen and inflammatory cells in periodontal disease” [Morfometrijska analiza kolagena i inflamatornih ćelija u periodontalnoj bolesti]. Vojnosanit pregl 2015; 72(3): 219-224. (DOI:10.2298/VSP130627076G) - Editorial (Vojnosanitetski Pregled)
The authors and their affiliations were listed as follows: Ranko Golijanin*†, Bojan Kujundžić†, Zoran Milosavljević‡, Dragan R. Milovanović§††, Zlatibor Andjelković║, Miroslav Obrenović¶, Radivoje Nikolić**†† *Department of Dentistry, ‡Department of Histology and Embriology, §Department of Pharmacology and Toxicology, **Department of Surgery, Faculty of Medical Sciences, University of Kragujevac, Kragujevac, Serbia; †Faculty of Dental Medicine, ¶Faculty of Medicine, University of East Sarajevo, Foča, Republic of Srpska, Bosnia and Herzegovina; ††Clinical Center “Kragujevac”, Kragujevac, Serbia Listed the authors and their affiliations should read as: Ranko Golijanin*†, Bojan Kujundžić†, Zoran Milosavljević‡, Dragan R. Milovanović§††, Zlatibor Andjelković║, Miroslav Obrenović¶, Radivoje Nikolić**†† *Department of Dentistry, ‡Department of Histology and Embriology, §Department of Pharmacology and Toxicology, **Department of Surgery, Faculty of Medical Sciences, University of Kragujevac, Kragujevac, Serbia; ║Department of Histology, Faculty of Medicine, University of Priština, Kosovska Mitrovica, Serbia; †Faculty of Dental Medicine, ¶Faculty of Medicine, University of East Sarajevo, Foča, Republic of Srpska, Bosnia and Herzegovina; ††Clinical Center “Kragujevac”, Kragujevac, Serbia Link to the corrected article 10.2298/VSP130627076G